Pengaruh Content Marketing, Brand Awareness, dan Persepsi Harga terhadap Keputusan Pembelian Produk Lip Cream Hanasui pada e-commerce Tiktok Shop di Kalangan Generasi Z - Hanifah Adilla Putri; Dhian Tyas Untari; Heni Rohaeni (Jurnal Manajemen Bisnis Era Digital, 2026)
This study aims to determine the influence of content marketing, brand awareness, and price perception on purchasing decisions of Hanasui lip cream products on Tiktok Shop e-commerce among Generation Z. The method used in this study is a quantitative method with purposive sampling technique as a sampling technique. This study used 105 respondents as research samples, with primary data obtained through distributing questionnaires to Gen Z consumers who have used and purchased Hanasui lip cream products on Tiktok Shop. The results of the study show that: (1) content marketing has a positive and significant effect on purchasing decisions, (2) brand awareness has a positive and significant effect on purchasing decisions, (3) price perception has a positive and significant effect on purchasing decisions, and (4) content marketing, brand awareness, and price perception simultaneously have a positive and significant effect on purchasing decisions of Hanasui Lip Cream products on Tiktok Shop e-commerce.